Risk of stroke and transient ischaemic attack after herpes zoster. (June 2016) - Kwon, S.U.; Yun, S.-C.; Kim, M.-C.; Kim, B.J.; Lee, S.H.; Lee, S.-O.; Choi, S.-H.; Kim, Y.S.; Woo, J.H.; Kim, S.-H.
Abstract: We assessed the association of herpes zoster (HZ) with stroke/transient ischaemic attack (TIA) in the general population according to age with controlling risk factors for stroke, using a nationwide representative cohort. The study was based on a prospective dynamic cohort consisting of 1 million Koreans representing all age groups, genders and geographical areas in the Korea Health Insurance Database. New events of stroke/TIA and HZ were identified using the diagnostic codes in the International Classification of Diseases, tenth revision. The risk for stroke/TIA after HZ was compared with HZ-free stroke/TIA individuals according to age group. A total of 766 179 adults were followed up for 11 years from 2003. The incidence of the first-diagnosed HZ cases was 9.40 per 1000 person-years, and that of the first-diagnosed stroke/TIA cases was 9.77 per 1000 person-years. The risk for stroke/TIA was higher in patients who had previous HZ episodes than in those who had never experienced HZ (incidence rate ratio 1.90; 95% CI 1.85–1.95). In addition, this risk persisted for several years after HZ. The risk of stroke/TIA after HZ gradually decreased with age; adjusted hazard ratio (HR) 2.04 in 18- to 30-year-olds, HR 1.74 in 30- to 40-year-olds, HR 1.43 in 40- to 50-year-olds, HR 1.23 in 50- to 60-year-olds, HR 1.24 in 60- to 70-year-olds, and HR 1.29 in those >70 years old, after controlling risk factors for stroke/TIA. Our findings provide evidence that HZ carries an increased risk of stroke or TIA and that the effect of HZ on stroke decreases with increasing age.